Encoding audio motion: spatial impairment in early blind individuals - Finocchietti, Sara; Cappagli, Giulia; Gori, Monica (Frontiers in Psychology, 2015)
The consequence of blindness on auditory spatial localization has been an interesting issue of research in the last decade providing mixed results. Enhanced auditory spatial skills in individuals with visual impairment have been reported by multiple studies, while some aspects of spatial hearing seem to be impaired in the absence of vision. In this study, the ability to encode the trajectory of a 2 dimensional sound motion, reproducing the complete movement, and reaching the correct end-point sound position, is evaluated in 12 early blind individuals, 8 late blind individuals, and 20 age-matched sighted blindfolded controls. Early blind individuals correctly determine the direction of the sound motion on the horizontal axis, but show a clear deficit in encoding the sound motion in the lower side of the plane. On the contrary, late blind individuals and blindfolded controls perform much better with no deficit in the lower side of the plane. In fact the mean localization error resulted 271 ± 10 mm for early blind individuals, 65 ± 4 mm for late blind individuals, and 68 ± 2 mm for sighted blindfolded controls. These results support the hypothesis that i) it exists a trade-off between the development of enhanced perceptual abilities and role of vision in the sound localization abilities of early blind individuals, and ii) the visual information is fundamental in calibrating some aspects of the representation of auditory space in the brain.